Postexercise fructose-maltodextrin ingestion enhances subsequent endurance capacity - Maunder, E.; Podlogar, T.; Wallis, G. A. (Medicine & Science in Sports & Exercise, 2018)
PURPOSE: Restoring skeletal muscle and hepatic glycogen content during short-term (<6 h) recovery from prolonged exercise is pertinent for athletes seeking to maximize performance in repeated exercise bouts. Previous research suggests that coingestion of fructose-glucose carbohydrate sources augments hepatic and has equivalent effects on skeletal muscle glycogen storage during short-term recovery from prolonged exercise compared with isocaloric glucose ingestion. The aim of the present investigation was to determine whether this has a discernible effect on subsequent exercise capacity.